Boosting employee motivation with loving- kindness - REB, Jochen (Institutional Knowledge at Singapore Management University, 2021)
New research at SMU, conducted by Professor Jochen Reb and his collaborators, Assosiate Professor William Tov and PhD student Theodore Masters-Waage, shows that loving-kindness can increase employee motivation and cultivate a positive mental state. This can impact job performace and job satisfaction.